ANALISIS RISIKO PRODUKSI AGROINDUSTRI BERAS (Studi Kasus: CV. Karma Indah Kabupaten Kolaka, Sulawesi Tenggara) - Prihantini, Campina Illa; Kasmiati, Kasmiati; Amin, Muhtar (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This study aims to determine the source of the risk of rice agroindustry production in CV. Karma Indah and analyze what factors influence the risk of rice agroindustry production in CV. Karma Indah. This research was carried out from March 2022 to April 2022 at CV. Beautiful Karma. Determination of the sample is done by purposive method, namely three people who were chosen deliberately, while the data analysis method used in this study is the expert opinion method and multiple linear regression analysis with the Cobb-Douglas function. Sources of production risk in rice agroindustry in CV. Karma Indah is supply, raw material price, demand and product price. Production factors supply, raw material prices and demand are included in the high-risk category, while product prices are included in the medium risk category. Supply factors, raw material prices and demand have a significant effect on the rice production process in CV. Karma Indah while the product price factor has no significant effect on the rice production process in CV. Karma Indah